Mobile application for recovering paralysis patient’s motion - Anuntachai, Anuntapat; Jantamongkollert, Thiti; Sungkhawijit, Mathurin (My University, 2018)
Paralysis is a symptom when patient’s central nervous system is failure because of blood deficiency. The patients cannot comfortably move their bodies due to muscle hyposthenia. The restoration requires regularly physical therapy which needs high accuracy because muscles have dysfunctional. This thesis represents the mobile application which help to muscle restoration of paralysis patient. This mobile application improves accuracy and efficiency of physical therapy. The physical therapy and muscle operation principles are collected and analyzed by this mobile application then collaborates with iBeacons sensors which properly control paralysis patient’s motion.
Keywords: IBeacons sensors; Mobile Application; Movement; Paralysis; Physical therapy